AB0271 Rs12218 polymorphism in saa1 gene in the russian population of ra patients is associated with secondary amyloidosis. a pilot study. (12th June 2018) - Krylov, M.; Muraviev, Y.; Alekseeva, A.; Samarkina, E.; Guseva, I.; Konovalova, N.; Varlamov, D.
Abstract : Background: Secondary amyloidosis (SA) is a serious complication of rheumatoid arthritis (RA), which is often fatal. Identification of associated risk factors, including genetic ones, is an important task. Objectives: To assess the role of SAA1 gene polymorphism, encoding serum amyloid-A, as a risk factor predisposing to SA in the sample of Russian RA patients. Methods: The study included 60 patients with RA, fulfiled the American College of rheumatology criteria (ACR) 1987. Of these 35 (mean age 49.5±10.8 y, mean disease duration 18.5±8, 9) developed SA manifestations, confirmed histologically: group SA (+). 25 patients (mean age 56, 7±11, 7 y, mean disease duration 16.3±7, 5 y) did not have either clinical or histological SA signs: group SA(-). The control group (C) consisted of 65 healthy employees. SAA1 gene polymorphism rs12218 (−13 T/C), mapped in the 5' flanking region of the gene, was studied in 125 subjects by polymerase chain reaction in real time (RT-PCR) with subsequent melting curves analysis. Results: Statistically significant differences in the rates of TT, TC and CC genotypes of rs12218 polymorphism were established between SA(+) group and the controls (17.1%, 64.0%, 48.6% and 38.5%, 46.1%, 15.4%, respectively, p=0.029). High rate (58.6%) of the mutant C allele in SA(+) group compared to the control group (38.5%) predetermines high risk of susceptibility to SA in RA patients [(OR 2.26, 95% CI(1.20–4.28), p=0.010]. Significant differences in rs12218 polymorphism rates were found between SA(+) and SA(-) groups [p<0.001]. The frequency of TC +CC genotype was significantly higher in the SA (+) group compared to SA(-) group [82.9% vs 36.0%, p<0.001]. The risk of predisposition to SA development among RA patients was increased when C allele frequencies in the group with SA (58.6%) were compared with the group without SA (22.0%) [OR 5.01, 95% CI (2.07–12.58), p<0.001]. No significant differences were found in the frequencies of genotypes and rs12218 alleles between SA(-) pts and the controls (p>0.05). Conclusions: Our data confirm that genetic polymorphism rs12218 in SAA1 gene, is associated with the development of secondary amyloidosis in RA patients and mutation in this gene is an important risk factor predisposing to the development of this severe complication in the Russian population. Disclosure of Interest: None declared